In my Isabelle theory I have a matrix with a constant factor:
...
k :: 'n and c :: 'a
(χ i j. if j = k then c * (A $ i $ j) else A $ i $ j)
I can calculate the transposed matrix:
(transpose (χ i j. if j = k then c * (A $ i $ j) else A $ i $ j))
In my eyes the latter should be equivalent to
(χ i j. if i = k then c * (A $ j $ i) else A $ j $ i))
by the definition of transpose
. But this is not true. What is my error here?
By the way, the definition of transposed is:
definition transpose where
"(transpose::'a^'n^'m ⇒ 'a^'m^'n) A = (χ i j. ((A$j)$i))"